Changes in the remuneration system for psychiatric care in Japan - Ito, H. (Die Psychiatrie, 2011)
Japan’s psychiatric care is reimbursed according to official prices called “national fee schedule,” which is revised once every 2 years. Fee schedule revisions have had a major influence on medical service providers in Japan, where the rate of private health care institutions is high. The increase of acute beds in inpatient care and the fee schedule for outpatient care have been promoted since the 1990’s. As a result, inpatient care has diverged into acute care units and geriatric units focused primarily on long-term care. In addition, outpatient care services have increased dramatically. Under these circumstances, some key challenges faced by Japan’s psychiatric care include poorly defined catchments areas and how to improve the evaluation of health care quality. Furthermore, the degree to which psychiatric care should assume the responsibility of geriatric care in Japan’s super-aging society remains a topic of debate.
Keywords: Remuneration system; policy; psychiatric care